The Tolerance Differences of Two Industrial Hemp Varieties Under Lead (Pb) Stress - Yanping Xu; Anuwat Kumpeangkeaw; Xia An; Xuan Chen; Yuan Zhang; Pin Lv; Qingying Zhang; Rong Guo; Qingqing Ji; Ming Yang (Toxics)
Industrial hemp is a crop with a high tolerance and accumulation of lead (Pb). Improving the Pb tolerance and accumulation capacity of industrial hemp is of great scientific and practical importance. This study utilized a pot with soil contaminated with Pb to investigate the differences in Pb tolerance between two industrial hemp varieties, Yunma1 (YM) and Shaanxi Industrial Hemp (SM), under Pb stress. The results indicated that Pb mainly accumulates in the roots of YM and SM (70–80%), with YM having a higher Pb accumulation than SM. It is worth nothing that under high Pb concentration conditions (5000 mg/kg), the Pb accumulation capacity of YM is twice that of SM. Accumulation characteristics of Pb in different plant tissues followed the pattern: roots > stems > leaves > fibers > seeds. In YM, approximately 70% of the absorbed Pb was fixed in the roots and 30% was transported to the above-ground parts. In contrast, SM transported more than 50% of absorbed Pb by roots to the above-ground areas, causing some degree of damage to stems and leaves. Even when Pb concentrations exceed 4000 mg/kg, YM exhibits strong tolerance (tolerance index greater than 90%), with normal growth and no signs of toxicity. However, SM showed a tolerance level of < 50% at high Pb concentrations, with significant heavy metal toxicity symptoms in the above-ground areas. These results provide important information for the remediation of Pb contaminated soils in mining areas.